Effects of nutritional supplements on explosive lower limb performance in volleyball players: a systematic review and network meta-analysis - Du, H.; Liu, S.; Li, M.; Zhao, K.; Jiang, W.; You, T.; Wang, Z.; Zou, D.; Shu, J.; Liu, C. (Nutrients, 2025)
Background: Explosive lower limb power, a critical determinant of success in volleyball, is a prime candidate for focused research. Consequently, nutritional supplements are commonly employed to gain an ergogenic edge. Despite this widespread practice, a comprehensive and evidence-based ranking of supplements for improving this key attribute is lacking, leaving athletes and practitioners without targeted evidence to guide decisions.